Novel Palestine Nation through the Works of Ibrahim Nasrallah - Parr, Nora (New Directions in Palestinian Studies, 2023)
Palestinian writing imagines the nation not as a nation-in-waiting but as a living, changing structure that joins people, place, and time into distinct formations. Novel Palestine examines these imaginative structures so that we might move beyond the idea of an incomplete or fragmented reality and speak frankly about the nation that exists and the freedom it seeks. Engaging the writings of Ibrahim Nasrallah, Nora E. H. Parr traces a vocabulary through which Palestine can be discussed as a changing and flexible national network linking people across and within space, time, and community. Through an exploration of the Palestinian literary scene subsequent to its canonical writers, Parr makes the life and work of Nasrallah available to an English-language audience for the first time, offering an intervention in geography while bringing literary theory into conversation with politics and history. "A welcome demonstration of the power of writing to redefine the political domain." - LYNDSEY STONEBRIDGE, author of We Are Free to Change the World: Hannah Arendt's Lessons in Love and Disobedience "An opportunity to reconsider and reinterpret the dominant discourses and motifs of Palestinian culture." - JOSEPH R. FARAG, author of Politics and Palestinian Literature in Exile "A must-read for everyone interested in Palestine, identity, and literature." - WEN-CHIN OUYANG, author of Politics of Nostalgia in the Arabic Novel "Novel Palestine stakes a claim about the relation between Palestinian literary writing and how it figures the experience of being Palestinian in excess of the terms of the settler state, its linear narrative and critical forms." - JEFFREY SACKS, author of Iterations of Loss: Mutilation and Aesthetic Form, al-Shidyaq to Darwish "Within a tradition of literary criticism charted by authors like Mary Layoun and Barbara Harlow." - NAJAT RAHMAN, author of In the Wake of the Poetic: Palestinian Artists after Darwish